Underwater signal analysis-submarine detection [microfilm] - Matthew Reginald Alexander (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia/ATMA, 2001